2011
DOI: 10.1177/1545109710397891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Psychoeducative Intervention on Adherence to HAART among Low-Literacy Patients in a Resource-Limited Setting: The Case of an Arab Country—Morocco

Abstract: Research has demonstrated that strict adherence is necessary to maximize highly active antiretroviral therapy (HAART) benefits. This is particularly challenging for low-literacy populations in resource-limited settings like Morocco and motivated the implementation of a psychoeducative program for patients under HAART at Rabat University Hospital. The study aimed at assessing the program's impact on adherence to antiretroviral medication, knowledge of HIV/AIDS and HAART, quality of life, and biological paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…9–31,93 Two of the studies reported mortality as an outcome, 9,10 22 reported morbidity, 930 1 on retention in care, 19 2 on quality of life, 15,20 and 1 on prevention of HIV transmission, 31 with some studies reporting on multiple outcomes. One article included information on the costs associated with providing adherence counseling and support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9–31,93 Two of the studies reported mortality as an outcome, 9,10 22 reported morbidity, 930 1 on retention in care, 19 2 on quality of life, 15,20 and 1 on prevention of HIV transmission, 31 with some studies reporting on multiple outcomes. One article included information on the costs associated with providing adherence counseling and support.…”
Section: Resultsmentioning
confidence: 99%
“…10,12,13,15,17 Effective interventions include provider-delivered adherence counseling, 13,15,16,24 food supplementation, 11 treatment supporters, 10 adherence support from community health workers, 12,20,21 and mobile phone text messages. 17,23 The evidence for directly observed therapy was mixed with some studies finding a positive association with adherence and clinical outcomes 22,26 and other studies finding no association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, a 3–5 session intervention aimed at providing educational and psychological support to low literacy patients, conducted in Morocco, showed no significant change in adherence, although there was a significant increase in CD4 T-cell counts and improved HIV suppression. 13 In Los Angeles, a small-scale randomized controlled trial was conducted to test an adherence enhancement program for low-income people living with HIV assumed to have lower health literacy. 14 This intervention consisted of small group sessions and one-on-one counseling to increase participants’ knowledge and communication skills.…”
mentioning
confidence: 99%
“…Although risk perception was high, knowledge of available treatments and ART was low. Other studies from the region have also reported low awareness of ART within the general population and among PLWHA [36], but efforts to promote awareness and access to ART remain limited in Jordan and the wider MENA region [37]. …”
Section: Discussionmentioning
confidence: 99%